Peronosporales Species Associated with Strawberry Crown Rot in the Czech Republic - Pánek, Matěj; Maňasová, Marie; Wenzlová, Jana; Zouhar, Miloslav; Mazáková, Jana (Journal of fungi (Basel, Switzerland), 2022)
The symptoms of crown rot on strawberry plants are considered typical for the pathogen Phytophthora cactorum, which causes high losses of this crop. However, an unknown number of related species of pathogens of Peronosporales cause symptoms quite similar to those caused by P. cactorum. To determine their spectrum and importance, strawberry plants were sampled from 41 farms in the Czech Republic. The cultures were isolated from the symptomatic plants using the baiting method, with subsequent cultivation on a semiselective medium. Isolates were identified to the species level using nuclear ribosomal internal transcribed spacer (ITS) barcoding after preliminary morphological determination. In total, 175 isolates of 24 species of Phytophthora, Phytopythium, Pythium, and Globisporangium were detected. The most represented was Phytophthora cactorum, with 113 (65%) isolates, which was recorded in 61% of farms, and the Pythium dissotocum complex with 20 (11%) isolates, which was recorded in 27% of farms. Other species were represented in units of percent. Large differences between farms in the species spectra were ascertained. The differences between species in cardinal growth temperatures and different management of the farms are discussed as a main reason for such a diversification. Regarding the dissimilar sensitivity of various species of Peronosporales against fungicides, the proper determination of the cause of disease is of crucial significance in plant protection.
Keywords: root pathogens; oomycetes; strawberry disease; root rot; Phytophthora cactorum